The effect of a high-carbohydrate diet on the skill performance of midfield soccer players after intermittent treadmill exercise - Abt, G.; Zhou, S.; Weatherby, R. (Journal of Science and Medicine in Sport, 1998)
This study examined the effect of a high-carbohydrate diet on the performance of dribbling and shooting skills of recreational soccer players. Six male midfield soccer players first completed 60 minutes of intermittent treadmill exercise, followed either by a mixed or a high-carbohydrate diet for 48 hours. A modified Zelenka Functional Performance Test was then administered, followed by the intermittent treadmill exercise and another skills test. Subjects then repeated the protocol two weeks later under the alternative dietary regime. Blood samples were obtained pre exercise and after each procedure for Hematocrit and concentrations of hemoglobin, plasma glucose and lactate. Heart rate was recorded during and after each procedure. Repeated measures MANOVA revealed (1) the skill performance was not impaired by the intermittent treadmill exercise (p > 0.05); (2) the high-carbohydrate diet did not increase the ability of players to shoot or dribble (p > 0.05); (3) a significant increase in heart rate during the post treadmill exercise skill test compared with that during the pre treadmill exercise test (p < 0.05); (4) a significant order by time effect for hematocrit (p < 0.05); (5) no significant differences in plasma glucose, plasma lactate or hemoglobin concentrations between tests (p > 0.05); and (6) a significant decrease in body mass from pre to post dietary regime within both conditions (p < 0.05). It is speculated that either (1) muscle glycogen depletion may not impair the ability of the player to execute game skills; (2) an alternative fatigue mechanism such as dehydration or increased lactate production may be causative factors in the reduction in skill performance; or (3) the treadmill protocol employed failed to induce a degree of glycogen depletion or fatigue large enough to cause a significant fall in skill performance.